2016
DOI: 10.1016/j.soilbio.2016.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis reveals ammonia-oxidizing bacteria respond more strongly to nitrogen addition than ammonia-oxidizing archaea

Abstract: Shifts in microbial communities driven by anthropogenic nitrogen (N) addition have broad-scale ecological consequences. However, responses of microbial groups to exogenous N supply vary considerably across studies, hindering efforts to predict community changes. We used meta-analytical techniques to explore how amoA gene abundances of ammonia-oxidizing archaea (AOA) and bacteria (AOB) respond to N addition, and found that N addition increased AOA and AOB abundances by an average of 27% and 326%, respectively. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
76
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 198 publications
(93 citation statements)
references
References 87 publications
12
76
5
Order By: Relevance
“…Our results indicate that genetic variation in the foliar chemistry of a foundation tree species may be an important factor influencing this niche differentiation. Our results contrast with a recent meta-analysis showing that amoA gene abundance of AOB was more responsive to N additions than that of AOA, and that increased nitrification potential with N addition was only correlated with AOB (Carey et al 2016). A potential caveat to this conclusion is that qPCR cannot distinguish between live, dead, or dormant (inactive) DNA.…”
Section: Contrasting Differences In Aoa and Aob Responsescontrasting
confidence: 99%
See 4 more Smart Citations
“…Our results indicate that genetic variation in the foliar chemistry of a foundation tree species may be an important factor influencing this niche differentiation. Our results contrast with a recent meta-analysis showing that amoA gene abundance of AOB was more responsive to N additions than that of AOA, and that increased nitrification potential with N addition was only correlated with AOB (Carey et al 2016). A potential caveat to this conclusion is that qPCR cannot distinguish between live, dead, or dormant (inactive) DNA.…”
Section: Contrasting Differences In Aoa and Aob Responsescontrasting
confidence: 99%
“…The linear decline in potential nitrification rates mirrored the linear decline of AOA abundance with increasing foliar CT concentrations across the Populus hybridization gradient but there was no trend in AOB abundance, suggesting AOA played a dominant role in nitrification in these forest ecosystems. However, our study system differs from most of the studies included in the Carey et al (2016) metaanalysis in two fundamental ways. However, several studies have demonstrated that amoA gene abundance derived from qPCR varies in response to factors that also affect nitrification rates (Carey et al 2016).…”
Section: Contrasting Differences In Aoa and Aob Responsesmentioning
confidence: 99%
See 3 more Smart Citations